2011
DOI: 10.1038/nn.2941
|View full text |Cite
|
Sign up to set email alerts
|

Pain sensitivity and vasopressin analgesia are mediated by a gene-sex-environment interaction

Abstract: Quantitative trait locus mapping of chemical/inflammatory pain in the mouse identified the Avpr1a gene, encoding the vasopressin-1A receptor (V1AR), as responsible for strain-dependent pain sensitivity to formalin and capsaicin. A genetic association study in humans revealed the influence of a single nucleotide polymorphism (rs10877969) within AVPR1A on capsaicin pain levels, but only in male subjects reporting stress at the time of testing. The analgesic efficacy of the vasopressin analog, desmopressin, revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 39 publications
7
99
2
1
Order By: Relevance
“…As might be expected given this interaction, genes (quantitative trait loci) with sex-dependent effects on pain trait variability have been uncovered [38][39][40][41][42] . A recent study uncovered a three-way interaction in both mice and humans between sex, genetics (AVPR1A genotype (AVPR1A encodes the vasopressin 1A receptor)) and acute stress 43 . Recent mouse studies have revealed another surprising factor that interacts with sex to modulate pain: social interaction.…”
Section: Male Onlymentioning
confidence: 99%
See 1 more Smart Citation
“…As might be expected given this interaction, genes (quantitative trait loci) with sex-dependent effects on pain trait variability have been uncovered [38][39][40][41][42] . A recent study uncovered a three-way interaction in both mice and humans between sex, genetics (AVPR1A genotype (AVPR1A encodes the vasopressin 1A receptor)) and acute stress 43 . Recent mouse studies have revealed another surprising factor that interacts with sex to modulate pain: social interaction.…”
Section: Male Onlymentioning
confidence: 99%
“…The distinction between the latter two types can be considered the difference between 'quantitative' and 'qualitative' sex differences. Although attention has mostly been paid to documenting quantitative sex differences in pain, a growing number of examples of qualitative differences in pain have been reported 31,39,43,[53][54][55][56][57][58][59][60][61][62][63][64] , and these promise to be far more important in the long run. As a practical matter, analgesics are routinely titrated according to their effect, which will effectively mitigate any sex differences along with other sources of inter-individual variability.…”
Section: Male Onlymentioning
confidence: 99%
“…This same phenomenon was thereafter demonstrated in high-and low-autotomy mouse strains 126 . In one of our studies, a particularly robust strain difference in pain sensitivity 127 was found eventually to exist only because of SIA-resulting simply from being placed in the testing room itself-in one strain but not the other; if mice were habituated to the room on several days before testing no strain difference was observed 36 . These sorts of findings have led to a discussion as to whether reproducibility in animal experiments would be enhanced by standardization of husbandry and experimental parameters across laboratories 128 .…”
Section: The Impact Of Laboratory Environmental Factorsmentioning
confidence: 55%
“…Also unappreciated is the fact that stress associated with pain testing can be surprisingly high (and hugely variable) in human participants as well. In a study of capsaicin pain, self-reported stress levels ranged from 0 to 8 on a 0-to-10-point scale, and this stress interacted with both sex and a genetic variant within the AVPR1A gene to significantly affect pain ratings 36 . Some laboratory stressors (or non-stressful modulatory factors) are related to husbandry, and have long been known.…”
Section: Jeffrey S Mogilmentioning
confidence: 99%
“…The vasopressin receptor has been linked to strain-dependent pain sensitivity to formalin and capsaicin 266 and oxytocin activation ameliorates visceral pain in particular 267 .…”
Section: Functional Vasopressin Receptors Were Absent From All Cell Lmentioning
confidence: 99%